(untitled) (Conferencea, 2022)
The article understands that most of the anthroponyms are nominatively motivated based on the animistic, totemistic and fetishistic ideas of ancient people about the spiritual world, the other world, the forces and phenomena of nature, the animal and plant worlds, the bird world.